2020
DOI: 10.1111/icad.12447
|View full text |Cite
|
Sign up to set email alerts
|

Is light pollution driving moth population declines? A review of causal mechanisms across the life cycle

Abstract: The night‐time environment is increasingly being lit, often by broad‐spectrum lighting, and there is growing evidence that artificial light at night (ALAN) has consequences for ecosystems, potentially contributing to declines in insect populations. Moths are species‐rich, sensitive to ALAN, and have undergone declines in Europe, making them the ideal group for investigating the impacts of light pollution on nocturnal insects more broadly. Here, we take a life cycle approach to review the impacts of ALAN on mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
2
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 204 publications
(266 reference statements)
1
86
2
9
Order By: Relevance
“…(34,(42)(43)(44). Similarly, there is mounting evidence that light pollution is driving local declines in suburban and urban locations (45,46). Although not an emphasis of the 11 articles, urbanization is increasingly recognized as an important stressor (47,48).…”
Section: What's In This Special Issue?mentioning
confidence: 99%
“…(34,(42)(43)(44). Similarly, there is mounting evidence that light pollution is driving local declines in suburban and urban locations (45,46). Although not an emphasis of the 11 articles, urbanization is increasingly recognized as an important stressor (47,48).…”
Section: What's In This Special Issue?mentioning
confidence: 99%
“…Until recently, light pollution had received less attention as a component of global change than other phenomena such as global warming, but a growing number of studies have now revealed the numerous and negative biological consequences of this light at night on many organisms (Hölker et al ., 2010; Gaston et al ., 2014; Bennie et al ., 2016). Insects seem particularly affected by artificial light at night, which has consequences at individual, population and ecosystem levels (Desouhant et al ., 2019; Boyes et al ., 2021). Artificial light at night has also been identified as a factor that could drive the decline of insect populations (van Langevelde et al ., 2018), raising questions about their conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, light pollution can be enhanced when more urban areas are surrounding the sampling site. Artificial light at night has major effects on nocturnal insect communities, disrupts the development of insects at different life stages (Boyes et al 2020 ), affects their fitness directly by reducing optical efficiency and orientation, and desynchronizes their internal clock (Owens and Lewis 2018 ). So, there are multiple possible reasons that might explain the observed patterns in β-diversity.…”
Section: Discussionmentioning
confidence: 99%